Influence of anxiolytic premedication on vasovagal reactions and home readiness following outpatient intrathecal anaesthesia - a retrospective analysis - Gebhardt, Volker; Kiefer, Kevin; Weiß, Christel (Acta anaesthesiologica Scandinavica, 2019)
Background: Vasovagal reactions during application of intrathecal anaesthesia (IA) are associated with high anxiety levels. A high percentage of patients undergoing outpatient surgery suffer from anxiety. Anxiolytic premedication in day-surgery is suspected to delay recovery and discharge and is, therefore, not routinely used. The aim of this retrospective analysis was to detect the influence of anxiolytic premedication on the incidence of vasovagal reactions and time until discharge home. Methods: Anaesthesia records of all patients undergoing outpatient surgery under low-dose IA from January 2008 to June 2017 were analysed. Incidences of vasovagal reactions with a decrease in blood pressure and/or heart rate and need for cardiovascular activating medications were documented. Patients were categorised as having received an anxiolytic premedication or not. The time from intrathecal injection of the local anaesthetic until readiness for discharge was recorded. Results: The records of 2747 patients were analysed. One thousand two hundred and ninety-one of them received an anxiolytic premedication of 1-2 mg midazolam intravenously. Three hundred and fourteen patients had vasovagal incidents during application of IA (no premedication n = 217 [15.0%], premedication n = 97 [7.5%], P < 0.0001). Premedication did not prolong time to achieve readiness for discharge (mepivacaine: P = 0.5886, chloroprocaine: P = 0.1555). However, in the prilocaine group, premedication led to a significantly earlier achievement of readiness for discharge (P = 0.0002). Conclusion: Anxiolytic premedication significantly reduces the incidence of vasovagal reactions during the application of IA and does not affect time until readiness for discharge.